Contribution of Acinetobacter-derived cephalosporinase-30 to sulbactam resistance in Acinetobacter baumannii - Kuo, Shu-Chen; Lee, Yi-Tzu; Yang Lauderdale, Tsai-Ling; Huang, Wei-Cheng; Chuang, Ming-Fen; Chen, Chien-Pei; Su, Shey-Chiang; Lee, Kuan-Rong; Chen, Te-Li (Frontiers in Microbiology, 2015)
The sulbactam resistance rate in Acinetobacter baumannii has increased worldwide. Previous reports have shown that the β-lactamase blaTEM-1 confers resistance to sulbactam in A. baumannii. The purpose of this study was to examine whether other β-lactamases including, the Acinetobacter-derived cephalosporinase (ADC), OXA-23, OXA-24/72, and OXA-58 families, also contribute to sulbactam resistance in A. baumannii. The correlation between these β-lactamases and the sulbactam minimal inhibitory concentration (MIC) was determined using A. baumannii clinical isolates from diverse clonality, which were collected in a nationwide surveillance program from 2002 to 2010 in Taiwan. A possible association between the genetic structure of ISAba1-blaADC-30 and sulbactam resistance was observed because this genetic structure was detected in 97% of sulbactam-resistant strains compared with 10% of sulbactam-susceptible strains. Transformation of ISAba1-blaADC-30 into susceptible strains increased the sulbactam MIC from 2 to 32 μg/ml, which required blaADC-30 overexpression using an upstream promoter in ISAba1. Flow cytometry showed that ADC-30 production increased in response to sulbactam, ticarcillin, and ceftazidime treatment. This effect was regulated at the RNA level but not by an increase in the blaADC-30 gene copy number as indicated by quantitative PCR. Purified ADC-30 decreased the inhibitory zone created by sulbactam or ceftazidime, similarly to TEM-1. In conclusion, ADC-30 overexpression conferred resistance to sulbactam in diverse clinical A. baumannii isolates.